Extraindo compromissos de responsabilidade social corporativa na mineração de agregados em São Paulo - Pereira, Renata Cherém de Araújo (2019)
The purpose of this thesis was to understand how market, state and civil society representatives involved in corporate social responsibility in aggregate mining negotiate their interests. For this, this work was based on the theoretical framework based on the literature on political corporate social responsibility. This served as a basis for selecting and deepening the other topics covered in the theoretical foundation: evolution of the concept of corporate social responsibility, aggregate mining, the rise of sustainability and the need for corporate social responsibility in mining. The qualitative, inductive, procedural and data-oriented approaches were used. In relation to the research strategy, a single case study was carried out. 58 in-depth interviews were conducted with market, State and civil society representatives. The documents provided by the interviewees collaborated to deepen the information. The data collected were analyzed using the constant comparison method in which categories are formed. The categories answered the objectives of this study. The research concludes that there is a process of formation of behavior patterns of the market, the State and civil society for the creation and maintenance of actions of corporate social responsibility. Among the main contributions of this study are the naturalization of conflicts by the market and the State, the veiled protagonism of the State in the development of corporate social responsibility and market positioning in an environment where the rules are not clear.